Carbon based dots capped tin oxide nanosheets hybridizing with silver nanoparticles for ultra-sensitive surface enhanced raman scattering substrate. (December 2020) - Wang, Qian; Chen, Mingming; Zhang, Jiaxin; Yu, Ting; Fu, FengFu; Dong, Yongqiang
Abstract: Carbon based dots capped tin oxide nanosheets (SnO2 /CDs) were synthesized by liquid exfoliation of tin oxide (SnO2 ) nanoparticles in the presence of single-layer carbon based (CDs). The obtained SnO2 /CDs have lateral sizes of about 20–50 nm and heights of about 3–4 nm. A thin layer of CDs of about 1–2 nm in thickness are presence on the surface of the SnO2 nanosheets. The SnO2 /CDs present excellent surface enhanced Raman spectroscopy (SERS) activity due to the chemical enhancement (CM) led by the charge transfer between SnO2 /CDs and the target molecules. The enhancement factor (EF) of the SnO2 /CDs is 1.42 × 10 5, taking rhodamine 6G as a model target molecule. The SnO2 /CDs are further hybridized with silver nanoparticles (AgNPs) using an in situ synthesis method. The obtained homogeneous nano-hybrids (SnO2 /CDs@AgNPs) have a lot of nanogaps. The nanogaps among the AgNPs/CDs create strong electromagnetic enhancement (EM) due to the "hot spots" effect. The nanogaps among the SnO2 /CDs and AgNPs/CDs allow the target molecules to be embedded, and thus gained both the CM effect of SnO2 /CDs and the EM effect of AgNPs/CDs. As a result, the as-prepared SnO2 /CDs@AgNPs exhibits excellent SERS activities, with an ultrahigh enhancement factor of 3.27 × 10 11 . Graphical abstract: Tin oxide nanosheets covered with carbon based dots are synthesized and further hybridized with silver nanoparticles (AgNPs) to prepare a novel surface enhanced Raman spectroscopy (SERS) substrate with an excellent SERS activity. Image 1